The Effect of Product Reviews and Content Marketing on Purchasing Decisions at T'samie Noodle Bar Restaurant - Usman, Syafiq; Andriyansyah, Mohamad Rheyfan; Santoso, Moh.; Rahmadi, Rahmadi (Indonesian Journal of Advanced Research, 2025)
This study examines how T'samie Noodle Bar Restaurant customers' judgements about what to buy are influenced by product reviews and content marketing. Multiple linear regression analysis was used in a quantitative way to build a causal associative descriptive design. One hundred individuals were chosen at random from among social media users who had made repeat purchases. Data was gathered using a Likert scale questionnaire, and its validity and accuracy were examined. The results showed that while product reviews had a significant impact (β = 0.257), content marketing had a bigger impact (β = 1.006). The two factors accounted 61.5% of the variation in buying decisions. These results suggest that review management and an efficient content strategy are crucial elements of culinary marketing.